2004
DOI: 10.1093/protein/gzh035
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cyclodextrin glucanotransferase as an antistaling enzyme by error-prone PCR

Abstract: In an effort to improve the properties of cyclodextrin glucanotransferase (CGTase) as an antistaling enzyme, error-prone PCR was used to introduce random mutations into a CGTase cloned from alkalophilic Bacillus sp. I-5 (CGTase I-5). A mutant CGTase[3-18] with the three mutations M234T, F259I and V591A was selected by agar plate assay. Sequence alignment of various CGTases indicated that M234 and F259 are located in the vicinity of the catalytic sites of the enzyme and V591 in the starch binding domain E. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 11 publications
1
52
0
Order By: Relevance
“…The A231/F260/F184 residues at the +1/+2 subsites are completely conserved in CGTases but are replaced by other amino acids at the same position in R-amylases (36) ( Table 1). Mutations at these subsites have previously highlighted this acceptor region to be essential in the determination of the reaction specificities of GH clan H enzymes (19,(37)(38)(39)(40)(41)(42). The drastic reduction of cyclization activity by these moderately bulkier substitutes A231T/V, A231V/F260W, may be explained by the inefficiency of the final step of the transglycosylation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The A231/F260/F184 residues at the +1/+2 subsites are completely conserved in CGTases but are replaced by other amino acids at the same position in R-amylases (36) ( Table 1). Mutations at these subsites have previously highlighted this acceptor region to be essential in the determination of the reaction specificities of GH clan H enzymes (19,(37)(38)(39)(40)(41)(42). The drastic reduction of cyclization activity by these moderately bulkier substitutes A231T/V, A231V/F260W, may be explained by the inefficiency of the final step of the transglycosylation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…3) (Bosma et al, 2002). Excretion of enzyme variants into the surrounding solid media containing substrate also allows for the rapid identification of improved variants by enlarged halo formation compared to wild-type enzyme (Shim et al, 2004). An alternative to this relatively simple plate assay is the screening of each individual member of the library in 96/384/1536-well microtitre plates (Fig.…”
Section: Screening and Selectionmentioning
confidence: 99%
“…A combination of epPCR and site directed mutagenesis were applied in an effort to generate CGTase variants from alkalophilic Bacillus sp. I-5 with improved properties as an antistaling enzyme (Shim et al, 2004). A triple mutant was created M234T/F259I/V591A, with a 10-fold decrease in cyclization activity and 15-fold increase in hydrolyzing activity.…”
Section: Evolving Product and Reaction Specificitymentioning
confidence: 99%
“…It was reported that two mutant protease genes of Bacillus subtilis were obtained by error-prone PCR, their catalytic efficiency was respectively 256 and 131 folds higher than the native enzyme ARNOLD, 1991 and. SHIM et al (2004) cloned a cyclodextrin glucose transferase gene from Bacillus I-5, and got a mutant gene containing three-point mutations (M234T, F259I and V591A) by error-prone PCR; as a result its cyclic activity was dramatically reduced by 10 folds, and the hydrolytic activity was enhanced by 15 folds (SHIM et al, 2004). Errorprone PCR and point-mutation method were used to obtain high acid resistance of mutant (T353I and H400R) of alpha amylase from Bacillus licheniformis, it was found that the mutants had stronger resistance than the native amylase under low pH value (LIU et al, 2012).…”
Section: Introductionmentioning
confidence: 99%